A Nanodrop Spectrophotometric Method and Stability Indicating for Determination of Amlodipine Besylate in Pharmaceutical Formulations of Kurdistan of Iraq - Qasim, Faroq O.; Mohammed, Nidhal M. Sh. (Science Journal of University of Zakho, 2021)
A nanodrop spectrophotometric method was developed and validated for determination of amlodipine besylate (AB) in bulk and tablet dosage form. The maximum absorption of amlodipine was shown at 357 nm using acetonitrile as a solvent. The developed method was found to be linear (R2 = 0.9990) within the concentration range of 2-10 µg/mL. The precision study showed acceptable values of RSD% (less than 1%). LOD and LOQ values were found to be 0.34 and 1.14 µg/mL, respectively. Accuracy study showed good recovery 99% Awalodipine and 98.88% Amloneer, in locally commercial tablets. The present method was applied successfully for stability indicating study of AB in Awalodipine and Amloneer products manufactured in (Erbil and sulaymaniyah, respectively)/ Kurdistan of Iraq. The stability-indicating study was investigated under acidic, basic, oxidative, photolytic, and thermal conditions. The results of both products showed that AB is unstable in acidic, alkaline, and oxidative conditions under heating at 60℃ up to 5 hrs. While under photolytic and thermal conditions, the degradation percentage was less than 15% indicating to the stability of AB in both Awalodipine and Amloneer tablets according to International Conference on Harmonization (ICH) guideline of drugs. It can be concluded that the main factor that affects the degradation of AB is the passage of time.
Keywords: Amlodipine; Nanodrop spectrophotometer; Development; Validation; Stability Indicating